A general one-step approach for in situ decoration of MoS2 nanosheets with inorganic nanoparticles. Issue 3 (25th November 2014) - Cheng, Zehong; He, Benzhao; Zhou, Li
Abstract : Here we present a general and controllable protocol for the one-step synthesis of various MoS2 –INP nanohybrids by employing carboxylic MoS2 nanosheets as a versatile support. Abstract : Two dimensional MoS2 nanosheets decorated with inorganic nanoparticles (INPs) are emerging as novel MoS2 -based nanohybrids for tuning the intrinsic attributes of both components for fundamental research and technological applications. However, the design and fabrication of MoS2 –INP nanohybrids with a tailor-made structure and functions remain a significant challenge. Herein we report a general and controllable protocol for the one-step synthesis of various MoS2 –INP nanohybrids by employing carboxylic MoS2 (MoS2 –COOH) nanosheets as a versatile support. The obtained MoS2 –INP nanohybrids exhibit good dispersibility, high reactivity and excellent processability. The size, morphology and coverage density of INPs on the surface of MoS2 –COOH can be readily controlled by tuning the feed ratio. Control experiments reveal that the presence of carboxylic functional groups plays a key role in controlling the structure and properties of the resulting MoS2 –INP nanohybrids. In addition, ternary MoS2 -based nanohybrids can also be readily prepared by this approach, as exemplified by the synthesis of MoS2 –Fe3 O4 /Pt nanohybrids, which simultaneously exhibit excellent catalytic performance toward the reduction of 4-nitrophenol and favorable magnetic separation capability. Considering the simple fabrication process, high controllability of this protocol and excellent performance of the product, the present work opens up enormous opportunities for the large-scale production of diverse MoS2 -based nanohybrids for many technological applications.